Abatacept is effective in Chinese patients with LRBA and CTLA4 deficiency - Lu Yang; Xiuhong Xue; Xuemei Chen; Junfeng Wu; Xi Yang; Li Xu; Xuemei Tang; Mo Wang; Huawei Mao; Xiaodong Zhao (Genes and Diseases, 2021)
CTLA4 deficiency and LRBA deficiency are a group disorders of immune dysregulation that affect CTLA4 pathway. The patients mainly present with autoimmunity, antibody deficiency and recurrent infections. Here we reported three Chinese patients with LRBA and CTLA4 mutations. They all presented with chronic diarrhea, hypokalemia, organomegaly, recurrent infections, and hypogammaglobulinemia. Reduced Treg cells and increased percentage of circulating follicular helper T (cTfh) cells were revealed in these patients. Although steroid and immunoglobulin therapy were given, the enteropathy was persistent. Therefore, abatacept treatment was provided to these patients. They showed a marked improvement of enteropathy and gastrointestinal endoscopy showed alleviated inflammatory lesion and follicular hyperplasia. Furthermore, the frequency of cTfh cells was reduced after abatacept therapy. Taken together, targeted therapy with abatacept is a promising treatment modality for patients with LRBA and CTLA4 deficiency. The findings also suggest that the frequency of cTfh cells could serve as a marker for tracking disease activity and the response to abatacept therapy.